2020
DOI: 10.1142/s0219061319500132
|View full text |Cite
|
Sign up to set email alerts
|

Mice with finitely many Woodin cardinals from optimal determinacy hypotheses

Abstract: We prove the following result which is due to the third author.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 50 publications
0
26
0
Order By: Relevance
“…This will only be applied in X -premice M for some X ∈ P 1 (R) with x 0 ∈ X and as in the proof of Lemma 3.8 "least" refers to the least set in the well order of elements of M definable from x 0 which is given by (•, x 0 , •). In this case, the game G ϕ, is a variant of the Kechris-Solovay game in [11] (see also the game in [21,Lemma 2.3]) adapted as a model game. The winning condition is Π 1 2 , so the game G ϕ, is determined.…”
Section: Letmentioning
confidence: 99%
See 4 more Smart Citations
“…This will only be applied in X -premice M for some X ∈ P 1 (R) with x 0 ∈ X and as in the proof of Lemma 3.8 "least" refers to the least set in the well order of elements of M definable from x 0 which is given by (•, x 0 , •). In this case, the game G ϕ, is a variant of the Kechris-Solovay game in [11] (see also the game in [21,Lemma 2.3]) adapted as a model game. The winning condition is Π 1 2 , so the game G ϕ, is determined.…”
Section: Letmentioning
confidence: 99%
“…Afterwards, Neeman improved this in [22] even further and showed that for all n, the existence of M n (x) for all reals x implies determinacy of all n (< 2 − Π 1 1 ) sets. Concerning the other direction, Woodin (see [21]) showed that if Σ 1 n+1 games are determined, then M n (x) exists for all reals x, thus establishing a level-by-level characterization of projective determinacy in terms of the existence of inner models with large cardinals. Similar characterizations are known forprojective games of length (see [1] and [3]).…”
mentioning
confidence: 99%
See 3 more Smart Citations